Graphene-based nanomaterials for stimuli-sensitive controlled delivery of therapeutic molecules - Khakpour, Elnaz; Salehi, Saba; Naghib, Seyed Morteza; Ghorbanzadeh, Sadegh; Zhang, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
Stimuli responsive drug delivery has attracted tremendous attentions in the past decades. They provide spatial- and temporal-controlled release in response to different triggers, thus enabling highly efficient drug delivery and minimizing drug side effects. Graphene-based nanomaterials have been broadly explored and showed great potential in smart drug delivery due to their stimuli-responsive behavior and high loading capacity for an extended range of drug molecules. These characteristics are resulted from its high surface area, mechanical and chemical stability, and excellent optical, electrical and thermal properties. Their great and infinite functionalization potential also allows them to be integrated into several types of polymers, macromolecules or other nanoparticles, leading to fabrication of novel nanocarriers with enhanced biocompatibility and trigger-sensitive properties. Thus, numerous studies have been dedicated to graphene modification and functionalization. In current review, we introduce different graphene-based nanomaterials utilized in drug delivery, and discuss the most important advances in their functionalization and modification. Also, their potential and progresses in intelligent drug release in response to different types of stimuli either endogenous (PH, redox, oxidation) or exogenous (temperature, NIR radiation, electric field) will be debated.